Neutron diffraction as a precise and reliable method for obtaining structural properties of bulk quantities of graphene - Sofer, Zdeněk (2015)
Graphene based carbon materials have attracted a great deal of attention in the last decade; nowadays tons of graphene are produced yearly. However, there is lack of precise and reliable techniques for the determination of structural properties of graphene on the bulk scale. The analytical methods being routinely applied for graphene characterization, including TEM and AFM, can be only used for the study of scant amounts of graphene samples and do not give general information on the average number of layers and the structure of the prepared graphenes. On the other hand, diffraction methods can be advantageously used to obtain information on the average thickness of the produced graphene as well as on the average sheets lateral dimensions, without the necessity of sample dispersion in solvents. We present a study of the structural properties of graphene prepared by chemical and thermal reduction of graphite oxide, comparing SEM, STEM, AFM, Raman spectroscopy, BET, X-ray and neutron diffraction methods. Our study brings new deep insights into the basic structural properties of graphene in a bulk form. Given the importance of a suitable characterization technique on the bulk materials, we wish to highlight the importance of these diffraction techniques for accurate determination of the graphene thickness and lateral parameters.